The OAS and the Promotion and Protection of Human Rights - LeBlanc, Lawrence J. author. aut Link
179 p. 1 illus.
Keywords: This book is a product of my long-standing interest in international action on human rights, an interest which I developed as a graduate student and which I have maintained as a teacher and researcher. I am indebted to Professor Vernon Van Dyke of the University of Iowa for stimulating my interest in the subject and for guiding the preparation of my Ph. D. thesis, of which this book is a greatly revised and expanded version. I should also like to express my ap preciation to Professor A. Glenn Mower, Jr. , of Hanover College, and to my colleague Glenn N. Schram, both of whom read the thesis and made many helpful suggestions when I began to revise it for publication. The book is im proved as a result of their efforts, though I alone remain responsible for any errors of fact or interpretation. Most of the research on the book was done at the Columbus Memorial Library of the OAS in Washington, D. C. , and I am grateful to the librarians there for kind and efficient assistance. The Marquette University Committee on Research provided me with a research grant for the summer of 1974 and supplementary grants in 1975 and 1976 which facilitated the completion of the manuscript: I am grateful for this assistance. I have endeavored to include all material available to me as of the end of March, 1976.